Notes on natural and cultural factors in the pre-Hispanic sociopolitical development of the northwest of Guanacaste, Costa Rica - Hurtado de Mendoza, Luis; Alvarado, Guillermo E. (Revista de Biología Tropical, 2021)
Introduction: Interdisciplinary studies on ancient occupation patterns and the development of human society in the Orosí Volcano region are few. Environmental data are included in archaeological studies of specific sites, mainly to illustrate the likely availability of local subsistence resources, with little regard for biodiversity linked to altitude and an array of different geomorphic areas. Effects surging from volcanic activity and tectonics are largely dispensed. Incidence of all these natural phenomena is rarely considered as agents of sociopolitical changes. Objective: Herein a search is performed in order to detect and illustrate instances of the relationship between sociopolitical change detected by archaeology and diverse natural and cultural factors as described by other scientific disciplines. Methods: A sample of 111 cultural components in archaeological sites were examined in terms of their geographical location, ecological context and chronological position along the periods of the cultural sequence in the Guanacaste region. Results: As settlement models, the archaeological data are confronted with diverse natural and cultural factors looking for their potential incidence as agents for sociopolitical change. Instances of relationship are examined and their apparent effects are evaluated for each period, both in preceramic and ceramic times. Conclusions: Both soil quality and climate are identified as important factors for change and development. Yet, largely salient are distinct cultural factors, namely the exchange of products, agriculture and migration processes.